Pengaruh Pemberian Insentif dan Komitmen Organisasi terhadap Disiplin Kerja Pegawai Puskesmas Gandrungmangu 2 Kabupaten Cilacap (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This research is motivated by several problems as follows: Employee work discipline is still not optimal, judging from the aspect of employee attendance is still lacking. There are still many employees who go home before the specified time. The level of employee discipline is still minimal because employees have double jobs such as having work practices at home, so they are required to come to another workplace before the end of work hours. The non-implementation of the sanctions made made employees of the Gandrungmangu II Health Center often come to work late, do not come to the health center without providing information, do not participate in morning and evening apples and abuse working hours for other purposes. Employee discipline in complying with work regulations has also not been maximized. Thus, the purpose of this study is to find out and analyze the influence of incentives and organizational commitment on the work discipline of employees of the Gandrungmangu 2 Health Center in Cilacap Regency. The method used is quantitative descriptive. The results of the study show that the provision of incentives has a positive and significant effect on employee work discipline. If the provision of incentives is carried out in accordance with the provisions, then work discipline will increase. Organizational commitment has a positive and significant effect on employee work discipline. If the organization's commitment increases, then work discipline will increase. The provision of incentives and organizational commitment has a positive and significant effect on employee work discipline. If the provision of incentives and organizational commitment increases, then work discipline will increase.